Dismantling Arabic Epistemology: Badawi's Codification in the Sight of al-Jabiri - Ibrahim Achmad Farrel Mahardika (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This article discusses the codification of classical Arabic whose main focus is to reveal Mohammad Abed al-Jabiri's critical epistemological thinking that the Arabic language codification process is not just an act of linguistic effort, but there are ideological elements that play an important role in shaping the way Muslims think. Al-Jabiri assesses the standards set by the Arabic language made by the Badawi community as the main reference because it is considered the most original and free from foreign influences. The epistimological impact of this action makes Arabic language that refers to the concrete, static, and non-historical Badawi world limits the capacity for abstraction, historicization, and rationalization in the Islamic intellectual tradition. This research uses a qualitative approach with a library research method. Primary data is obtained from al-Jabiri's work Al-Turats wa al-Hadatsah, while secondary data includes studies related to language codification, Arabic linguistic history, and relevant journals. The results show that the codification of Arabic language makes stagnation, and the disconnection between language and complex modern reality because the codification refers to Badawi society which is reflected in the lexical structure, semantics, and social imagination of Arab society. This article directs that the importance of reorienting Arabic language that is inclusive of the renewal of Islamic reason and civilization by rebuilding a more progressive Arabic language.